Patient information materials in general practices and promotion of health literacy: an observational study of their effectiveness - Protheroe, Joanne (Br J Gen Pract, 2015)
BACKGROUND: Government policy in the UK emphasises providing patients with good health information to encourage participation in their health care. Patient information leaflets (PILs) form part of this policy and have been shown to affect patient health outcomes; however, many are poorly written. AIM: To describe the PILs in general practice surgeries in Stoke-on-Trent in terms of readability and variety of content. DESIGN AND SETTING: An observational study of randomly selected GP practices (n = 17) across Stoke-on-Trent. METHOD: PILs were assessed for readability (Flesch Reading Ease and Flesch–Kincaid Grade Level) and compared with national skills level data and with the recommended level for medical information. The PILs were also categorised for content using the Rudd (2007) health material classification framework. RESULTS: A total of 345 PILs were collected and assessed. Only 24.3% meet recommended reading-level criteria. Compared with national skills levels, over 75% of the PILs collected were too complex for at least 15% of the English population. Of the PILs, 47.8% were classified as ‘systems navigation’ (information regarding services); 22.9% were disease prevention (screening and immunisations); 14.2% personal and public safety; and less than 10% were for managing illness or health promotion. CONCLUSION: Current PILs in general practices do not all promote health literacy. Information only accessible to a proportion of higher skilled patients may increase inequalities in health. Less than 10% of PILs promote managing illness or healthy lifestyles. Processes must be put in place to improve the readability and variety of content of PILs in GP practices.